2023
DOI: 10.1186/s13071-023-05964-1
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the mosquito-haemosporidian parasite-bird host network in the southwestern Iberian Peninsula: insights into malaria infections, mosquito community and feeding preferences

Carlos Mora-Rubio,
Martina Ferraguti,
Sergio Magallanes
et al.

Abstract: Bakground Vector-borne diseases affecting humans, wildlife and livestock have significantly increased their incidence and distribution in the last decades. Because the interaction among vectors-parasite-vertebrate hosts plays a key role driving vector-borne disease transmission, the analyses of the diversity and structure of vector-parasite networks and host-feeding preference may help to assess disease risk. Also, the study of seasonal variations in the structure and composition of vector and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 111 publications
0
4
1
Order By: Relevance
“…In addition, since traps in the zoological garden operated during a shorter period than in the rest of the localities, our sampling size in this area could be affected. However, this fact is not expected to affect the conclusions obtained based on the extremely low prevalence of avian Plasmodium found in these species here and in other previous studies [ 50 , 51 ].…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…In addition, since traps in the zoological garden operated during a shorter period than in the rest of the localities, our sampling size in this area could be affected. However, this fact is not expected to affect the conclusions obtained based on the extremely low prevalence of avian Plasmodium found in these species here and in other previous studies [ 50 , 51 ].…”
Section: Discussioncontrasting
confidence: 46%
“…Indeed, for the case of field-collected mosquitoes in other regions of Spain, previous studies revealed a total absence of avian Plasmodium in Cs. longiareolata [ 50 , 51 ]. However, Mora-Rubio et al [ 51 ] found DNA of the related Haemoproteus parasites, which may be mainly transmitted by other insect groups (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations